PENGEMBANGAN E-SYSTEM MANAJEMEN DATA SISWA DAN KEUANGAN SEKOLAH BERBASIS WEB STREAMLIT - Faiz Rizqi Hanafi; Auzriel Zidan Arby; Lilis Roudhotul Jannah; Muhammad Rizky Ramadhan; Milani Nuril Sandi; Nandang Adriansyah; Shanasha Aulia Dianthi; Syerikha Ananda; Thio Mandala Putra; Zaqhluul Farhan; Nardiono (Abdi Jurnal Publikasi, 2026)
The rapid development of information technology has encouraged educational institutions to adopt digital systems to improve administrative efficiency and data accuracy. However, many schools still rely on manual or semi-digital processes, particularly in managing student data and school financial administration. This condition was found at Sekolah Plus Pelita Insani Parung, where administrative and financial records were managed using spreadsheets, resulting in data duplication, reporting delays, and limited integration between student and financial data. This community service activity aims to develop a web-based e-system for student data and school financial management using the Streamlit framework, equipped with automated administrative reporting features. The implementation method included initial consultation, field observation, system design and development, system implementation, and training for administrative and financial staff. The developed system supports multi-user access, integrated student and financial data management, automated report generation, and data visualization to assist decision-making. The results show that the developed e-system successfully improves the efficiency and accuracy of administrative and financial data management. School staff were able to generate periodic reports more quickly and manage data in a centralized and structured manner. This system contributes to the digital transformation of school administration and enhances transparency and accountability in financial management.